Significance of the distolingual vestibule and lingual aspects of the mandible in prosthodontics: An in vivo study - Isha Rastogi; Prima Patel (Wolters Kluwer Medknow Publications, 2023)
Introduction: Managing and treating severely resorbed ridges is a challenge for the dentist. Especially, in older geriatric patients who have this problem. Till now, the classification by Neil is well accepted by all for the distolingual vestibule region and lingual area. Materials and Methods: We studied 500 patients with the presence of mandibular second molar teeth aged 20-50 years. The mirror method and a special instrument were used to view the section of the distolingual aspect present in the lingual area as well as the oral cavity. Results: The records were seen and studied well for the class and lingual region present. Conclusion: The distolingual alveolar sulcus and lingual region in the mandible are a guide for the tray to be used. We recorded this region in the patients by our technique.